PELATIHAN PEMBUATAN MINYAK ATSIRI DAUN PSIDIUM GUAJAVA L. MELALUI PROSES DESTILASI DI DESA MEGANG SAKTI III KECAMATAN MEGANG SAKTI - Wahyu Arini; Tri Ariani (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2021)
Currently, many aromatic essential oils are developed from various types of leaves found in Indonesia. One of the leaves that have the potential to produce aromatic essential oils is guava leaf. Various guava leaves have been widely used as essential oils, but there is a new variety of guava leaves that has not been used as essential oil, namely crystal guava leaves. Crystal guava leaves have many benefits because crystal guava leaves contain several volatile compounds and have a strong distinctive aroma, so guava leaves have the potential to produce essential oils. The crystal guava plant is one of the leading commodities in Megang Sakti III Village, this is indicated by the many crystal guava plantations throughout the Megang Sakti III District, besides that the use of crystal guava leaves is still relatively mediocre, as if it is only used as a diarrhea medicine and the rest is not used. thus attracting the interest of TIM in carrying out PPM activities in the village by training in making essential oil from guava leaves using the distillation process. Essential oils are oils obtained from plant parts by means of steam distillation or water distillation. Essential oil from crystal guava leaves is very potential to be used as an antimicrobial and antioxidant.